Abelson phosphorylation of CLASP2 modulates its association with microtubules and actin. Issue 3 (12th March 2014) - Engel, Ulrike; Zhan, Yougen; Long, Jennifer B.; Boyle, Scott N.; Ballif, Bryan A.; Dorey, Karel; Gygi, Steven P.; Koleske, Anthony J.; VanVactor, David
<x xml:space="preserve">Abstract</x> The Abelson (Abl) non‐receptor tyrosine kinase regulates the cytoskeleton during multiple stages of neural development, from neurulation, to the articulation of axons and dendrites, to synapse formation and maintenance. We previously showed that Abl is genetically linked to the microtubule (MT) plus end tracking protein (+TIP) CLASP in Drosophila. Here we show in vertebrate cells that Abl binds to CLASP and phosphorylates it in response to serum or PDGF stimulation. In vitro, Abl phosphorylates CLASP with a Km of 1.89 µM, indicating that CLASP is a bona fide substrate. Abl‐phosphorylated tyrosine residues that we detect in CLASP by mass spectrometry lie within previously mapped F‐actin and MT plus end interaction domains. Using purified proteins, we find that Abl phosphorylation modulates direct binding between purified CLASP2 with both MTs and actin. Consistent with these observations, Abl‐induced phosphorylation of CLASP2 modulates its localization as well as the distribution of F‐actin structures in spinal cord growth cones. Our data suggest that the functional relationship between Abl and CLASP2 is conserved and provides a means to control the CLASP2 association with the cytoskeleton. © 2014 The Authors. Cytoskeleton Published by Wiley Periodicals, Inc.